2018
DOI: 10.1590/1980-5373-mr-2017-0927
|View full text |Cite
|
Sign up to set email alerts
|

Boro-Austempering Treatment of Ductile Cast Irons

Abstract: Samples of ductile cast irons alloyed with Cu, Cu-Ni and Cu-Ni-Mo were austempered, borided and boro-austempered and characterized for hardness and micro-adhesive wear behavior. The kinetics of layer formation was also studied. The boriding method used was molten borax bath, in periods of 2 and 4 hours at temperatures of 850, 900 and 950 ºC. The direct austempering treatment was performed immediately following the boriding treatment (from 850, 900 and 950 ºC) using molten salt baths at temperatures of 240, 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
5
0
2
Order By: Relevance
“…Figures 4-A and 4-B show the layers obtained for reference steels after boro-austempering treatments. In both cases the obtained layers had thicknesses in the range of 85~90 microns, values similar to those obtained in ductile cast irons submitted to the same treatment[14]. The layers are composed of two regions, indicating a polyphase coating formation.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Figures 4-A and 4-B show the layers obtained for reference steels after boro-austempering treatments. In both cases the obtained layers had thicknesses in the range of 85~90 microns, values similar to those obtained in ductile cast irons submitted to the same treatment[14]. The layers are composed of two regions, indicating a polyphase coating formation.…”
supporting
confidence: 77%
“…Hu et al stated that the presence of molybdenum may decrease the amount of granular bainite transformed from the supercooled austenite, contributing to the formation of bainite laths [20]. In both cases the obtained layers had thicknesses in the range of 85~90 microns, values similar to those obtained in ductile cast irons submitted to the same treatment [14]. The layers are composed of two regions, indicating a polyphase coating formation.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…[24] The combination of austempering and boriding treatment is defined to be boro-austempering and has been applied successfully in cast irons. [25,26] From the viewpoint of reducing production cost, the integrated treatment of austempering and boriding is a potential alternative method to produce bainitic steels with higher hardness and better corrosion resistance. However, few studies on boro-austempering treatment of high-strength bainitic steels have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since the boro-austempering treatment is successfully applied in cast irons [20,21], it has attracted much attention. However, very limited studies have been performed to fabricate high-strength bainitic steels by boro-austempering [18,19].…”
Section: Introductionmentioning
confidence: 99%